2011
DOI: 10.1093/eurheartj/ehr336
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular pacing is superior to right ventricular pacing in bradycardia patients with preserved systolic function: 2-year results of the PACE trial

Abstract: Left ventricular adverse remodelling and deterioration of systolic function continues at the second year after RVA pacing. This deterioration is prevented by BiV pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 35 publications
4
84
0
6
Order By: Relevance
“…[13][14][15][16] It is also associated with adverse outcomes even for patients with bradycardia and preserved LVEF who had standard indications for RV pacing. 1,2,17) Furthermore, it is estimated that up to 40% of patients with permanent pacemakers have HF or LV systolic dysfunction because of frequent RV pacing and their underlying cardiac disease. 18) Thus, upgrading of RV pacing systems to CRT devices is often performed for patients who develop LV dysfunction due to RV pacing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] It is also associated with adverse outcomes even for patients with bradycardia and preserved LVEF who had standard indications for RV pacing. 1,2,17) Furthermore, it is estimated that up to 40% of patients with permanent pacemakers have HF or LV systolic dysfunction because of frequent RV pacing and their underlying cardiac disease. 18) Thus, upgrading of RV pacing systems to CRT devices is often performed for patients who develop LV dysfunction due to RV pacing.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that CRT is being developed as a realistic treatment option to prevent LV dysfunction induced by RV pacing, even for symptomatic patients with bradycardia and normal LVEF. [1][2][3] The adverse effects of RV pacing on patients with indications for RV pacing due to bradycardia may be prevented by CRT, but risk stratification of future LV dysfunction for such patients remains ambiguous. We therefore used a variety of patients, who had previously had had implantable cardioverter-defibrillators (ICD) implanted, to verify the following hypothesis; 1) the effect of RV pacing on LV performance including LVEF and LV dyssynchrony may differ depending on baseline LVEF; and 2) changes in LVEF during RV pacing correlate with those in LV dyssynchrony.…”
mentioning
confidence: 99%
“…These studies have tested "de novo" CRT implantation in patients with a conventional pacing indication, both with preserved left ventricular systolic function [67][68][69] and with moderate-severe left ventricular dysfunction [70][71][72]. The results suggest that CRT plays a preventive role with regard to HF mortality/hospitalizations only in patients with left ventricular dysfunction (LVEF <40%).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Pequeños estudios aleatorizados han señalado que los pacientes con disfunción del VI moderada-grave podrían beneficiarse de la TRC en lugar de la estimulación apical del VD convencional (tabla 15) [123][124][125][126][127][128][129][130] . En general, los objetivos primarios de estos estudios se sustituyeron por objetivos hemodinámicos.…”
Section: Estimulación Cardiaca Con Terapia De Resincronización Cardiaunclassified
“…No se observó diferencia significativa en cuanto a los objetivos clínicos de los dos grupos. Las mismas conclusiones se observaron a los 2 años de seguimiento 124 . El estudio PREVENT-HF 129 aleatorizó a 108 pacientes con BAV de alto grado a TRC o estimulación del VD con o sin DAI, y no mostró beneficio de la TRC en remodelado del VI a los 12 meses.…”
Section: Estimulación Cardiaca Con Terapia De Resincronización Cardiaunclassified